Florida's Indians from ancient times to the present - Milanich, Jerald T. (University Press of Florida, 1998)
"Florida's Indians tells the story of the native societies that have lived in Florida for twelve millennia, from the early hunters at the end of the Ice Age to the modern Seminole, Miccosukee, and Creek Indians." "When the first Indians arrived in what is now Florida, they wrested their livelihood from a land far different from the modern countryside, one that was cooler, drier, and almost twice the size. Thousands of years later European explorers encountered literally hundreds of different Indian groups living in every part of the state. (Today every Florida country contains an Indian archaeological site.) The arrival of colonists brought the native peoples a new world and great changes took place - by the mid-1700s, through warfare, slave raids, and especially epidemics, the population was almost annihilated. Other Indians soon moved into the state, including Creeks from Georgia and Alabama, who were the ancestors of the modern Seminole and Miccosukee Indians." "Written for a general audience, this book is lavishly illustrated with full-color drawings and photographs."--Jacket
Keywords: Indians of North America -- Florida.; Florida -- Antiquities.; Peuples autochtones -- Floride.; Floride -- Antiquités.; HISTORY -- State & Local.; Antiquities; Indians of North America; Florida; Gender & Ethnic Studies.; Social Sciences.; Ethnic & Race Studies.